2000
DOI: 10.2960/j.v26.a5
|View full text |Cite
|
Sign up to set email alerts
|

Variability of the Stratification and Circulation on the Flemish Cap duringthe decades of the 1950s-1990s

Abstract: Oceanographic observations on the Flemish Cap (around 47°N, 45°W) from the early-1990s to 1999 are compared to the long-term mean and to conditions during the past several decades. The mean temperature and salinity fields and their seasonal cycles were first computed and then used to construct T/S anomaly time series. The data shows a relatively warm time period from the 1950s through the 1960s and three colder-than-normal periods since the early-1970s. In general, it was found that variations in water propert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
38
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 11 publications
4
38
0
Order By: Relevance
“…The monthly mean model temperature and salinity anomalies at intermediate depths of 100-300 m over the shelf break of the ECS in the control run have significant low-frequency (time scales longer than one year) variations, which are consistent with previous observations made in the region (Petrie et al, 1992;Petrie and Drinkwater, 1993;Colbourne and Foote, 2000). The maximum monthly mean anomalies of sub-surface (100-300 m) temperature and salinity in the control run are about 1°C and 0.2, respectively, over the shelf breaks of the Labrador and northern Newfoundland shelves; and about 2°C and 0.5, respectively, over the shelf breaks of the southwestern Newfoundland and Scotian shelves.…”
Section: Interannual Variability Over the Eastern Canadian Shelf A Nusupporting
confidence: 80%
See 1 more Smart Citation
“…The monthly mean model temperature and salinity anomalies at intermediate depths of 100-300 m over the shelf break of the ECS in the control run have significant low-frequency (time scales longer than one year) variations, which are consistent with previous observations made in the region (Petrie et al, 1992;Petrie and Drinkwater, 1993;Colbourne and Foote, 2000). The maximum monthly mean anomalies of sub-surface (100-300 m) temperature and salinity in the control run are about 1°C and 0.2, respectively, over the shelf breaks of the Labrador and northern Newfoundland shelves; and about 2°C and 0.5, respectively, over the shelf breaks of the southwestern Newfoundland and Scotian shelves.…”
Section: Interannual Variability Over the Eastern Canadian Shelf A Nusupporting
confidence: 80%
“…The period with the most significant cooling events over the Newfoundland Shelf was 1966-71 which corresponds to the period of the "Great Salinity Anomaly" in the subpolar gyre (Dickson et al, 1988). Petrie et al (1992) and Colbourne and Foote (2000) suggested that the advection of Labrador Current water onto the Newfoundland Shelf was the main cause of the interannual variability observed over the region. Petrie et al (1992) also suggested that the large regional differences in the surface ice extent and advection over the Labrador and Newfoundland shelves could explain why the interannual variability in sea surface temperature (SST) over these two shelves is virtually uncorrelated.…”
Section: Review Of Circulation and Hydrographic Features On The Eastementioning
confidence: 99%
“…&! observations suggest that the amplitude of seasonal variations of freshwater in this region can be as large or larger than inter-annual variations (Petrie et al, 1991;Petrie et al, 1992;Colbourne and Foote, 2000). For perspective, seasonal salinity variations in the LC approach 0.5 near the surface along the eastern Grand Banks (Petrie et al, 1991).…”
Section: ! $!mentioning
confidence: 95%
“…This is a larger fraction of the total transport than has previously been attributed to the baroclinic component of the flow, but it also assumes that none of the 4.5 Sv of eastward flow crossing the ridge is fed by inshore branches of the circulation over the Grand Banks. Additionally, it is possible that part of the LC south of Flemish Pass arrives by flowing east of Flemish Cap, the pathway used by the DWBC (Colbourne and Foote, 2000). Because these waters also may !…”
Section: ! "%!mentioning
confidence: 99%
“…Temperature and salinity variability on Flemish Cap is given by Colbourne and Foote (2000). Accordingly, the upper layer water column on the Flemish Cap is nearly isothermal at a temperature of 3.5-4°C from late-January until April and remains at about 3.5-4°C throughout the year at depths below approximately 75 m. The phase of the seasonal temperature cycle is spatially coherent with the Newfoundland Shelf with warming in the upper layer commencing in early May and continuing to warm until late August to early September at a rate of about 0.1°C per day.…”
Section: Introductionmentioning
confidence: 99%